Hybrid surgery cutting using node snapping algorithm, real-time volume rendering and haptic feedback - Peng, J.; Li, Ling; Squelch, Andrew (2013)
We present a framework for interactive simulation of surgical cuts such as those being practiced in surgical treatment. Unlike most existing methods our framework is based on hybrid heterogeneous deformable models providing more flexibility. In order to keep the representation consistent, we apply 3-dimensional node snapping algorithm on the outer surface mesh to generate smooth cut without a large increase of element count, and employ a volumetric deformable model underneath the surface to present the internal structures and material properties of heterogeneous deformable objects. Haptic interaction is integrated into the simulation system to provide cutting tool as well as force feedback. The achieved quality and performance of the presented framework is demonstrated using human soft tissue models. © 2013 IADIS.